1996
DOI: 10.1007/s00585-996-1134-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency waves in the Earth's magnetosheath: present status

Abstract: Abstract. The terrestrial magnetosheath contains a rich variety of low-frequency (: proton gyrofrequency) fluctuations. Kinetic and fluid-like processes at the bow shock, within the magnetosheath plasma, and at the magnetopause all provide sources of wave energy. The dominance of kinetic features such as temperature anisotropies, coupled with the high-conditions, complicates the wave dispersion and variety of instabilities to the point where mode identification is difficult. We review here the observed fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 93 publications
4
135
0
Order By: Relevance
“…These peaks are likely related to the microscale physical processes taking place near these boundaries. In particular, several studies have reported intense wave activity and large amplitude magnetic field fluctuations within shock downstream regions (e.g., Schwartz et al, 1996;Bamert et al, 2004;Kataoka et al, 2005;Kajdič et al, 2012). The neighborhood of the ICME leading edge is a much less studied region in terms of plasma wave activity and plasma instabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These peaks are likely related to the microscale physical processes taking place near these boundaries. In particular, several studies have reported intense wave activity and large amplitude magnetic field fluctuations within shock downstream regions (e.g., Schwartz et al, 1996;Bamert et al, 2004;Kataoka et al, 2005;Kajdič et al, 2012). The neighborhood of the ICME leading edge is a much less studied region in terms of plasma wave activity and plasma instabilities.…”
Section: Discussionmentioning
confidence: 99%
“…We separate the aforementioned 1 h regions around the shock and the leading edge because these are the regions where important microscale physical processes are expected to take place (e.g., Schwartz et al, 1996;Lucek et al, 2005;Blanco-Cano et al, 2006;Yordanova et al, 2008;Desai et al, 2011). We emphasize that these regions are not stretched/compressed or otherwise modified for the superposed epoch analysis.…”
Section: Label Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of experimental works addressed the mirror modes using in-situ spacecraft data (for reviews see Schwartz et al, 1996, andTsurutani et al, 2011). A large majority of those studies, however, used either no ion measurements or only the measured moments of the distribution function.…”
Section: Introductionmentioning
confidence: 99%
“…Mirror modes and ion-cyclotron waves appear to be the two most important wave modes in the (Earth's) magnetosheath (e.g., Schwartz et al, 1996), which is confined between the bow shock and the magnetopause. Both wave modes are fed from the temperature anisotropy that is characteristic to the magnetosheath: higher temperature in the plane perpendicular to the magnetic field.…”
Section: Introductionmentioning
confidence: 99%